Impact of Sports Training On Physical and Psychological Development in Male Athlete - Bhagwan Singh Baghel; Dr. Chintan B. Patel (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research investigates the impact of structured sports training programmes on the physical and psychological development of male athletes, focusing on the intricate relationship between training intensity, frequency, and overall health, motivation, and mental resilience. Employing a mixed- methods approach, the research amalgamates quantitative data from athletes' performance metrics with qualitative insights gathered through psychological assessments and interviews. The findings reveal a significant correlation between higher training intensity and increased levels of physical fitness and psychological resilience, underscoring the importance of tailored training regimens that harmonise physical exertion with mental wellbeing. The study indicates that frequency of training sessions plays a crucial role in sustaining athletes' motivation and enhancing emotional stability. These results hold substantial significance in the field of healthcare, as they elucidate the dual benefits of sports training on both physical health and mental health among athletes, suggesting that structured training can serve as a viable intervention for promoting holistic wellbeing. The broader implications advocate for the integration of customised training programmes within healthcare frameworks as a strategy for improving not just athletic performance but also overall psychological health, thereby emphasising the need for a multidisciplinary approach to athlete development that encompasses both physical training and psychological support.
Keywords: Sports Training; Physical Development; Psychological Development; Male Athletes; Athletic Performance